Upaya Penurunan Kecacatan Painting Line 1 PT Astra Komponen Indonesia - Primayoka, Yudha Kresna; Felecia, Felecia (Jurnal Titra, 2015)
PT ASKI is motorcycle component manucaturer. The average of total NG products for 2015 is 23,64%, while for dirty spots is 11,4%. The companyâs NG targets for 2015 are only 12% for total NG and 6% for dirty spots. Therefore Quality Control Circle (QCC) methods will be applied to reduce NG products. The root cause for dirty spots are dirty environment in painting line facilities and tools. Operators dicipline to keep the environments clean also contributes to this problem. Therefore this research suggest to change spraymanâs gloves and masking tape paper. Dirty spots reduced by 1% from spraymanâs gloves changing, and 4% from masking tape -changing. Both result are not significant reduction to reach company NG targets. Other improvement sugesstion to be implemented are standarization on facilities and production equipments.